2022
DOI: 10.1093/oncolo/oyab003
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage Triple-negative Breast Cancer: Time to Optimize Personalized Strategies

Abstract: Triple-negative breast cancer (TNBC) accounts for approximately 15%-20% of breast cancers diagnosed worldwide, which amounts to almost 200 000 cases each year. Although historically TNBC is considered difficult to treat with a poor prognosis, there is emerging evidence showing excellent response rates in a subset of TNBC patients. Attempts to de-escalate chemotherapy in hormone-receptor-positive (HR+) and HER2-neu amplified breast cancer subtypes have been successful. At present, robust strategies to personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…It was also demonstrated that TIL levels were lower in pre-chemotherapy when compared to post-chemotherapy samples and this supports the hypothesis that chemotherapy could induce an antitumor immune response [ 113 ]. It has also been observed that, when using neoadjuvant chemotherapy ( NACT ), increased TILs were associated with higher pCR , regardless of the type and duration of NACT therapy [ 114 ]. Patients with high- TIL residual disease experienced a significantly better metastases-free survival ( MFS ) when compared with patients in the low- TIL group [ 113 ].…”
Section: Tumor Microenvironment Tumor Infiltrating Lymphocytes ( ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was also demonstrated that TIL levels were lower in pre-chemotherapy when compared to post-chemotherapy samples and this supports the hypothesis that chemotherapy could induce an antitumor immune response [ 113 ]. It has also been observed that, when using neoadjuvant chemotherapy ( NACT ), increased TILs were associated with higher pCR , regardless of the type and duration of NACT therapy [ 114 ]. Patients with high- TIL residual disease experienced a significantly better metastases-free survival ( MFS ) when compared with patients in the low- TIL group [ 113 ].…”
Section: Tumor Microenvironment Tumor Infiltrating Lymphocytes ( ...mentioning
confidence: 99%
“…TILs are reproducible biomarkers, and multiple studies have confirmed their prognostic value in TNBC ( Table 3 and Table 4 ) [ 114 ]. Immune response mediated by TILs is an important factor that has to be taken into consideration in treatment management; however, the presence or absence of particular subtypes and their ratio in cell population significantly influences the outcome.…”
Section: Tumor Microenvironment Tumor Infiltrating Lymphocytes ( ...mentioning
confidence: 99%
“…[1][2][3] Most TNBC patients are often diagnosed at more advanced stages because it lack conspicuous early-stage symptoms and specific diagnostic biomarkers. [4][5] Unfortunately, traditional chemotherapy faces many obstacles in TNBC treatment, such as poor chemo-sensitivity and severe chemo-resistance, leading to high recurrence and distant metastasis. [6][7][8] Therefore, DOI: 10.1002/adfm.202309524 overcoming or bypassing the chemoresistance/sensitivity is crucial for enhanced TNBC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, treatment options for TNBC were limited to cytotoxic chemotherapy. However, TNBC represents a highly heterogenous group of tumors, and understanding the molecular biology of a specific tumor allows for personalized treatment (in turn, minimizing unnecessary treatment toxicity while improving cancer outcomes) [ 4 ]. This article reviews the current landscape of curative-intent TNBC treatment strategies, in addition to looking ahead toward future directions and possible therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%